Storage stability of soy protein isolate powders containing soluble protein aggregates formed at varying pH - Fengxian Guo (Food Science & Nutrition, 2020)
Abstract Soy protein is wildly used in food industry due to its high nutritional value and good functionalities. However, the poor storage stability of commercial soy protein products has puzzled both the producers and the users for a long time. The current study assessed the changes in protein solubility, aggregation, oxidation, and conformation of soy protein isolate (SPI) with various soluble aggregates formed at different pH values (pH 5–8) during storage. During storage, SPI samples showed a reduced protein solubility (p < .05), an increased protein oxidation (p < .05), and an attenuated conformational enthalpy (∆H). SPI with a higher pH produced more disulfide‐mediated aggregates at the expense of sulfhydryl groups and experienced greater losses of protein tertiary structure and a faster reduction in solubility. Yet, all samples nearly shared similar rising trend during 8‐week storage, which indicated the production of protein carbonyls was insensitive to pH. Soluble aggregates present in fresh SPI samples appeared to induce instability of SPI during storage. These findings suggested SPI prepared at pH 6 was in favor of its storage stability, and soluble aggregates presented in fresh samples should be paid more attention for further study of storage stability kinetics.